WhatsApp as a disinformation platform: : Case study of the Brazilian presidential elections - Canavilhas, João; Colussi, Juliana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The next presidential elections in Brazil will take place in October 2022. It’s important to reflect on what happened in 2018 to avoid that the disinformation disseminated on social networks does not play a fundamental role in the democratic process again. This research verifies the degree of disinformation in content shared in family groups on WhatsApp related to the 2018 Brazilian presidential elections. After analyzing 393 contents with some level of disinformation concerning political issues, it was concluded that most material corresponds to a combination of parody or satire and fabricated content. It was corroborated that the dissemination of misleading content on WhatsApp during the elections was part of the campaign strategies of the winning candidate.